A Home-Based Palliative Care Consult Service for Veterans. (November 2016) - Golden, Adam G.; Antoni, Charles; Gammonley, Denise
We describe the development and implementation of a home-based palliative care consult service for Veterans with advanced illness. A retrospective chart review was performed on 73 Veterans who received a home-based palliative care consult. Nearly one-third were 80 years of age or older, and nearly one-third had a palliative diagnosis of cancer. The most common interventions of the consult team included discussion of advance directives, completion of a "do not resuscitate" form, reduction/stoppage of at least 1 medication, explanation of diagnosis, referral to home-based primary care program, referral to hospice, and assessment/support for caregiver stress. The home-based consult service was therefore able to address clinical and psychosocial issues that can demonstrate a direct benefit to Veterans, families, and referring clinicians.